THE EFFECT OF ABG BIO-ORGANIC FERTILIZER ON THE GROWTH AND PRODUCTION SWEET CORN (Zea mays saccharata Sturt) - Asmara Sari Nasution (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The research of the effect bio-organic fertilizer ABG on the growth and production of sweet corn (Zea mays saccharata Sturt) has been carried out by using a randomized block design (RAK) factorial with 2 factors and 3 replicates, namely: bio-organic liquid ABG fertilizer (A), compost (K) with a combination of treatments. The analytical methods used to conclute from the analysis of data using linear mathematical models. Observed parameters: plant height, stem diameter, number of leaves, leaf area, weight of cobs per sample and the length of the cob. ABG fertilizer application had no significant effect on all parameters were observed. Giving compost significant effect on plant height, number of leaves, leaf area and length of the cob, but did not significantly affect the stem diameter and weight of fruit per sample. Interaction ABG and compost fertilizer treatment had no significant effect on all parameters were observed.Keywords: bio-organic fertilizer, growth, production, corn